2015
DOI: 10.1094/phyto-01-14-0018-r
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Attenuated, Cross-Protective Pepino mosaic virus Variant Through Alignment-Guided Mutagenesis of the Viral Capsid Protein

Abstract: Mild variants of many viruses are able to protect infected plants from subsequent invasion by more severe variants of the same viruses through a process known as cross-protection. In the past, the cross-protective viral variants were commonly derived from mild field isolates that were sometimes genetically heterogeneous, providing variable levels of cross-protection. Here, we report a novel approach to rapidly generate cross-protective variants of the tomato-infecting Pepino mosaic virus (PepMV) independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…It was also suggested that cross-protection might play an important role in shaping population structures of RNA plant viruses 3 . Cross-protection refers to the specific protection against a virus in plants pre-inoculated with a mild isolate of the same virus 10 11 . Mechanistically, cross-protection was once thought to be caused by homology-based RNA silencing, although this notion has been challenged by several more recent studies 9 12 13 14 15 .…”
mentioning
confidence: 99%
“…It was also suggested that cross-protection might play an important role in shaping population structures of RNA plant viruses 3 . Cross-protection refers to the specific protection against a virus in plants pre-inoculated with a mild isolate of the same virus 10 11 . Mechanistically, cross-protection was once thought to be caused by homology-based RNA silencing, although this notion has been challenged by several more recent studies 9 12 13 14 15 .…”
mentioning
confidence: 99%
“…In general, our results support the finding of low genetic diversity, but geographical differentiation was counteracted by moderate gene flow. This knowledge could provide insights into fundamental eco‐evolutionary processes and valuable information for the design and implementation of stable and effective control strategies, such as cross‐protection by attenuated PepMV isolates (Agüero et al, ; Chewachong et al, ; Hanssen et al, ), which appears to be a good solution in the short term for managing this viral disease.…”
Section: Discussionmentioning
confidence: 99%
“…That complete establishment of the whole plant “cross protection” requires a substantial head start by the primary virus is not inconsistent with SIE operating at the cellular level. Rather, it suggests that most of the susceptible cells must be pre-occupied by the primary virus in order to block the invasion of the superinfector ( Chewachong et al, 2015 ; Zhang et al, 2015 ). Furthermore, once the cross protection is established, the superinfector genome could not be detected despite repeated attempts over many weeks ( Chewachong et al, 2015 ).…”
Section: Does Sie Operate At the Cellular Or Whole Plant Level?mentioning
confidence: 99%
“…Rather, it suggests that most of the susceptible cells must be pre-occupied by the primary virus in order to block the invasion of the superinfector ( Chewachong et al, 2015 ; Zhang et al, 2015 ). Furthermore, once the cross protection is established, the superinfector genome could not be detected despite repeated attempts over many weeks ( Chewachong et al, 2015 ). Together these studies suggest that the non-cell-autonomous SIE plays a minimal role in SIE manifestation.…”
Section: Does Sie Operate At the Cellular Or Whole Plant Level?mentioning
confidence: 99%
See 1 more Smart Citation